PENDIDIKAN ERA REVOLUSI INDUSTRI 4.0 MENUJU ERA SOCIETY 5.0 DI MASA PANDEMI COVID 19 - Kahar, M. Iksan; Cika, Hairuddin; Nur Afni; Nur Eka Wahyuningsih (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2021)
The learning system in the 4.0 revolution era that applies creativity, critical thinking, collaboration, communication skills, community and character skills, with several aspects and components of educational learning 4.0 So that to face learning in the industrial revolution 4.0, everyone must have critical thinking skills, knowledge and skills. digital literacy skills, information literacy, media literacy and mastering information and communication technology. Meanwhile, in facing the era of society 5.0, the world of education plays an important role in improving the quality of human resources. In addition to education, several elements and stakeholders such as the government, Community Organizations (Ormas) and the entire community also take part in welcoming the upcoming era of society 5.0. To answer the challenges of the industrial revolution 4.0 and Society 5.0 in the world of education, 21st century life skills or better known as the 4C (Creativity, Critical Thinking, Communication, Collaboration)